2015
DOI: 10.1038/nrclinonc.2015.99
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the management of advanced, ER-positive, HER2-negative breast cancer

Abstract: Hormone-receptor-positive breast cancer accounts for the majority-up to 80%-of all breast cancers. The evolution of breast cancer from early stage to the metastatic setting leads to increased heterogeneity, the occurrence of new mutations, and the development of treatment resistance representing a great challenge for management decisions. Unfortunately, little data exist to offer guidance in this context, and a reliance on traditional clinical parameters remains when deciding on optimal treatment. In advanced-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
93
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 85 publications
1
93
0
3
Order By: Relevance
“…Breast cancer is categorized into three subtypes according to estrogen receptor (ER), progesterone receptor (PR) and HER2 status: hormone receptor (HR)‐positive, HER2‐positive and triple negative subtypes . Of these, HR‐positive breast cancers constitute approximately 60%–70% . Endocrine therapy is considered to be the mainstay therapy for HR‐positive breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is categorized into three subtypes according to estrogen receptor (ER), progesterone receptor (PR) and HER2 status: hormone receptor (HR)‐positive, HER2‐positive and triple negative subtypes . Of these, HR‐positive breast cancers constitute approximately 60%–70% . Endocrine therapy is considered to be the mainstay therapy for HR‐positive breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to chemotherapy is still a problematic issue and challenging factor in the breast cancer treatment. [1] As a second common cause of cancer death in women, the importance of focusing on the underlying mechanisms of multidrug resistance (MDR) in breast cancer has been increased. [2] Therefore, in the last decade, considerable attention has been dedicated to the role played by multifactorial MDR.…”
mentioning
confidence: 99%
“…However, as BC is an extremely heterogeneous disease, resistance to treatment is a major clinical challenge for current BC management [1]. Therefore, the development of more specific biomarkers and recognition of new therapeutic targets would really contribute to solving the problems of therapy resistance and metastasis [2,3,4]. In recent years, an increasing number of clinical studies have suggested that an optimal vitamin D status has a protective effect against BC development and that high Vitamin D receptor (VDR) expression in breast tumors is associated with a better survival rate [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%